The View of Pediatric Nephrotic Syndrome as a Podocytopathy - Pedro Alves Soares Vaz de Castro; Thomas Fujihara Ide; Fernando Crespo Torres; Ana Cristina Simões e Silva (MDPI AG, 2023)
Nephrotic syndrome (NS) is a complex clinical entity characterized by proteinuria, hypoalbuminemia, and edema. In this review, we propose the view of NS as a podocytopathy, highlighting the importance of understanding the role of podocytes in the development of this condition. We discuss the various etiologies of NS, ranging from congenital to primary renal diseases, as well as secondary forms due to systemic diseases. We also delve into the mechanisms underlying podocyte injury, which plays a crucial role in the development of NS. By viewing NS as a podocytopathy, we suggest potential implications for the diagnosis and treatment of this condition, including the use of podocyte-specific biomarkers and targeted therapies. Our review provides a comprehensive overview of NS and its underlying mechanisms, emphasizing the importance of a multidisciplinary approach to the diagnosis and management of this condition. Further research is essential to better understand the complex interplay between podocyte injury and the development of NS, with the ultimate goal of improving patient outcomes.